Stratified cost-utility analysis of total hip arthroplasty in displaced femoral neck fracture - Igor Larrañaga; Iñigo Etxebarria-Foronda; Oliver Ibarrondo; Ania Gorostiza; Cristina Ojeda-Thies; Jose Miguel Martínez-Llorente (Elsevier, 2022)
Objective: To conduct a stratified cost-utility analysis of total versus partial hip arthroplasty as a function of clinical subtype. Method: All cases of this type of intervention were analysed between 2010 and 2016 in the Basque Health Service, gathering data on clinical outcomes and resource use to calculate the cost and utility in quality-adjusted life years (QALYs) at individual level. The statistical analysis included applying the propensity score to balance the groups, and seemingly unrelated regression models to calculate the incremental cost-utility ratio and plot the cost-effectiveness plane. The interaction between age group and American Society of Anesthesiologists (ASA) risk class was assessed in the multivariate analysis. Results: The study identified 5867 patients diagnosed with femoral neck fracture, of whom 1307 and 4560 were treated with total and partial hip arthroplasty, respectively. In the cost-utility analysis based on the seemingly unrelated regression, total hip arthroplasty was found to have a higher cost and higher utility (2465€ and 0.42 QALYs). Considering a willingness-to-pay threshold of €22,000 per QALY, total hip arthroplasty was cost-effective in the under-80-year-old subgroup. Among patients above this age, hemiarthroplasty was cost-effective in ASA class I-II patients and dominant in ASA class III-IV patients. Conclusions: Subgroup analysis supports current daily clinical practice in displaced femoral neck fractures, namely, using partial replacement in most patients and reserving total replacement for younger patients. Resumen: Objetivo: Realizar un análisis de coste-utilidad de la prótesis total de cadera frente a la prótesis parcial. Método: Se analizaron todos los casos intervenidos desde 2010 hasta 2016 en el Servicio Vasco de Salud, recogiendo resultados clínicos y uso de recursos para calcular individualmente el coste y la utilidad en años de vida ajustados por calidad (AVAC). El análisis estadístico incluyó el pareamiento por puntaje de propensión para balancear los grupos y modelos de regresión aparentemente no relacionados para calcular la razón de coste-utilidad incremental y el plano de coste-efectividad. La interacción de grupo de edad y riesgo según la American Society of Anesthesiologists (ASA) se incluyó en el análisis multivariante. Resultados: Se identificaron 1307 pacientes con prótesis total y 4560 con prótesis parcial. Al hacer el análisis de coste-utilidad con modelos de regresión aparentemente no relacionados el resultado fue mayor coste y mayor utilidad para la prótesis total (2465 € y 0,42 AVAC). Para un umbral de 22.000 € por AVAC, la prótesis total fue coste-efectiva en el subgrupo de menores de 80 años. En el grupo de mayores de 80 años la parcial fue coste-efectiva en los casos con riesgo ASA I-II y dominante en los ASA III-IV. Conclusiones: El análisis de subgrupos ratifica la práctica clínica habitual en las fracturas de cuello de fémur desplazadas de intervenir a la mayoría de los pacientes mediante prótesis parcial y reservar la prótesis total para los pacientes más jóvenes.